Advanced topics in quantum field theory : a lecture course - Shifman, M. (Cambridge : Cambridge University Press, 2012)
"Since the advent of Yang-Mills theories and supersymmetry in the 1970s, quantum field theory - the basis of the modern description of physical phenomena at the fundamental level - has undergone revolutionary developments. This is the first systematic and comprehensive text devoted specifically to modern field theory, bringing readers to the cutting edge of current research. The book emphasizes nonperturbative phenomena and supersymmetry. It includes a thorough discussion of various phases of gauge theories, extended objects and their quantization, and global supersymmetry from a modern perspective. Featuring extensive cross-referencing from traditional topics to recent breakthroughs in the field, it prepares students for independent research. The side boxes summarizing the main results and over 70 exercises make this an indispensable book for graduate students and researchers in theoretical physics"--
Machine generated contents note: Part I. Before Supersymmetry: 1. Phases of gauge theories; 2. Kinks and domain walls; 3. Vortices and flux tubes (strings); 4. Monopoles and skyrmions; 5. Instantons; 6. Isotropic ferromagnet: O(3) sigma model and extensions; 7. False vacuum decay and related topics; 8. Chiral anomaly; 9. Confinement in 4D gauge theories and models in lower dimensions; Part II. Introduction to Supersymmetry: 10. Basics of supersymmetry with emphasis on gauge theories; 11. Supersymmetric solitons; References; Index.
Includes bibliographical references and index.
Keywords: Quantum field theory; SCIENCE / Mathematical Physics